Assessment of vascular function: flow-mediated constriction complements the information of flow-mediated dilatation. Issue 2 (26th October 2009) - Gori, T; Grotti, S; Dragoni, S; Lisi, M; Di Stolfo, G; Sonnati, S; Fineschi, M; Parker, J D
Abstract : Objective: To determine whether vascular function assessed by low-flow-mediated constriction (L-FMC), a novel non-invasive method, complements the information obtained with "traditional" flow-mediated dilatation (FMD). Design and patients: In protocol 1, 12 healthy young volunteers underwent FMD and L-FMC measurements at rest and immediately after isometric exercise of the same hand. In protocol 2, 24 patients with coronary artery disease, 24 with congestive heart failure, 24 hypertensive patients and 64 healthy volunteers were enrolled to undergo L-FMC and FMD measurements. Results: In protocol 1, exercise was associated with mean (SD) increases in radial artery blood flow, diameter and L-FMC (from −5.1 (1.5)% to −7.8 (3.4)%, p<0.05), while FMD was significantly blunted (from 6.0 (2.4)% to 3.0 (3.2)%, p<0.05). In protocol 2, both FMD and L-FMC were blunted in the patient groups. Receiver operating curve analysis showed that, as compared with FMD alone, the combination of L-FMC and FMD significantly improved the sensitivity and specificity in detecting patients diagnosed with cardiovascular disease (p<0.05). Conclusion: In the first protocol, FMD and L-FMC were shown to be reciprocally regulated. A blunted FMD may, in certain cases, be an expression of increased resting vascular activation and not only of impaired endothelial function. In the second protocol, a statistical approach showed that implementation of L-FMC provides a better characterisation than FMD of vascular function in cardiovascular disease. Vascular (endothelial) function is a complex phenomenon which requires a multifaceted approach; it is suggested that a combination of L-FMC and FMD will provide additive and complementary information to "traditional" FMD measurements.